Blurring of vision due to VLM - Kamala, D.; Mahmud, Rohela; Abdullah, Khairul Anuar; Ibrahim, Jamaiah (Faculty of Medicine, University of Malaya, 1999)
A thirty two year old taxi driver presented with complaints of headache, nausea, vomiting and blurring of vision of the left eye of two days duration. He was found to have an acute anterior uveities and secondary glaucoma. On further examination patient was also found to have a neuroretinitis and phlebitis in the same eye. A worm was found in the anterior chamber and it was removed via a limbal incision under local anaesthesia. The worm-like structure sent to the Department of Parasitology was identified as Gnathostoma spinigerum. The patient was treated with topical eye drops and oral steroids at the same time to reduce the inflammation. No neurological symptoms were seen. The patient was not available for further evaluation and followup. (JUMMEC 1999; 2:115-116).